2015
DOI: 10.1111/jth.13134
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation assay using factor XIa to measure factors VIII and IX and their glycoPEGylated derivatives is robust and sensitive

Abstract: To cite this article: Waters EK, Hilden I, Sørensen BB, Ezban M, Holm PK. Thrombin generation assay using factor XIa to measure factors VIII and IX and their glycoPEGylated derivatives is robust and sensitive. J Thromb Haemost 2015; 13: 2041-52.Summary. Background: Conventional coagulation factor assays are associated with certain limitations, as they do not always reflect the clinical heterogeneity of bleeding in hemophilic patients or correctly reflect the individual patient response to treatment with bypass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…In addition, we found that FXIa-activated TGT is equally suitable for evaluation of FIX-deficiency and the assignment of potency of FIX-containing concentrates (manuscript in preparation). In agreement with our study, Waters et al found that a FXIa-activated TGT is more robust and sensitive than traditional TF-triggered TGT when applied for evaluation of FVIII-and FIX-spiked haemophilia A and B plasma samples [44]. Unlike Waters et al who added FXIa to the lipid reagent, we found that our TGT assay variant can be adapted from a commercially available TGT kit by spiking the substrate and calcium chloride reagent, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found that FXIa-activated TGT is equally suitable for evaluation of FIX-deficiency and the assignment of potency of FIX-containing concentrates (manuscript in preparation). In agreement with our study, Waters et al found that a FXIa-activated TGT is more robust and sensitive than traditional TF-triggered TGT when applied for evaluation of FVIII-and FIX-spiked haemophilia A and B plasma samples [44]. Unlike Waters et al who added FXIa to the lipid reagent, we found that our TGT assay variant can be adapted from a commercially available TGT kit by spiking the substrate and calcium chloride reagent, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…The thrombin generation assay (TGA) is a global haemostatic assay that provides a more complete picture of the coagulation process [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…By studying these two activators in parallel, the differences in TGA sensitivity can be teased out. The concentrations used for FIXa and FXIa TGA activation in this study (ie 5 nmol/L FIXa and 0.22 nmol/L FXIa) have been studied individually by members of our research team . The FIXa concentration used in this study was significantly lower compared to data from McIntosh et al (14 nmol/L FIXa), while the FXIa concentration was higher than that studied by Jha et al who used 15‐100 pM FXIa + 0.5 pM TF for TGA activation.…”
Section: Methodsmentioning
confidence: 61%
“…In haemophilia A plasma, activating the TGA using the intrinsic pathway with either FIXa or FXIa can make the assay highly sensitive to FVIII concentrations < 1%. Previous studies have shown that using either FIXa or FXIa activation, the TGA was more accurate and sensitive to FVIII levels well below 1% . However, no studies have compared FIXa and FXIa TGA activation in a parallel fashion.…”
Section: Introductionmentioning
confidence: 99%